A review on the pattern of electricity generation and emission in Malaysia from 1976 to 2008 - Shekarchian, M.; Moghavvemi, M.; Mahlia, T.M.I.; Mazandarani, A. (Elsevier, 2011)
Like many other countries, most of the power plants in Malaysia are using fossil fuel for electricity generation. In the past decade, thermal power plants generated about 89.3% of electricity and about 10.7% was generated by renewable sources such as hydropower. This study was conducted to chronicle 33 years of Malaysian electricity generation industry. The capacity of power generation installed and electricity generation from the years 1976 to 2008 has been gathered along with the total pollutant emissions and emission per unit electricity generation for each type of power plants. These were calculated using emission factors, and the pattern of electricity generation and emission production has been presented. The results show that using renewable energy and increasing the contribution of the combined cycle as a best type of thermal power plants and use more natural gas is recommended to reduce emission. © 2011 Elsevier Ltd. All rights reserved.